(untitled) (Research, Society and Development, 2022)
Education is not a mandatory subject in the Brazilian curriculum, but official curricular documents and legislation in the field of education highlight its importance in the formation of the contemporary subject and, in addition, affirm that it must be worked in an integrated and transversal way within of educational institutions, either with the disciplines, as well as in projects. Thus, the objectives of this work were to analyze seven works presented at the Interactive Science Space (EIC) workshop. For this, scientific meetings were held with the students within the EIC Science Club, which lasted from April to August, and in the last three months, September to November, the students worked on the development of projects to present them in the workshop held on the premises from the University of São Paulo (USP). The main results showed that club members were concerned with environmental issues, decided to study them, and acquired a speech in favor of awareness of environmental causes.